2020
DOI: 10.1061/(asce)gt.1943-5606.0002274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drilling for Tieback Anchors on Surrounding Ground: Results from Field Tests

Abstract: A full-scale field test program was carried out to investigate the effects of drilling for tieback anchors on the surrounding ground. The test anchors were drilled from the ground surface through a soft clay deposit and into bedrock. Five different drilling methods were compared. All methods caused excess pore pressures in the surrounding clay, up to 70 kPa, extending several meters away from where drilling took place. This impact on pore pressures was for most drilling methods significantly larger than what h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The results generally display a reduced pore pressure in the surrounding ground which could indicate that the air flushing caused an air-lift pump effect as suggested in case studies (Lande et al 2020;Ahlund and Ögren 2016;Bredenberg et al 2014). However, the limited dataset makes the analysis challenging and no clear conclusions can be drawn.…”
Section: Air Flushing Testsmentioning
confidence: 69%
See 2 more Smart Citations
“…The results generally display a reduced pore pressure in the surrounding ground which could indicate that the air flushing caused an air-lift pump effect as suggested in case studies (Lande et al 2020;Ahlund and Ögren 2016;Bredenberg et al 2014). However, the limited dataset makes the analysis challenging and no clear conclusions can be drawn.…”
Section: Air Flushing Testsmentioning
confidence: 69%
“…Other aspects that should be investigated are (1) the effect of drilling in a confined aquifer (e.g. under an impermeable soil layer) as frequently observed in the field (Lande et al 2020;Ahlund and Ögren 2016;Sandene et al 2020), (2) the influence of varying soil density, (3) different degrees of saturation and (4) the impact of different pile rotation rates. It is expected that refined tests will provide further insight into overburden drilling.…”
Section: Applicability Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahardjio (2017) observed high EPWP even 5 months from the installation of large group of jacked piles. Lande et al (2020) reported approximately 8 kPa EPWP remaining in soft clay 150 days after anchor drilling with uncased system was completed. In order to control the pile driving process, Tefera et al (2013) installed the piezometers in the area of potential failure plains.…”
Section: Introductionmentioning
confidence: 99%